2014
DOI: 10.1902/jop.2014.130661
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Glycated Hemoglobin Levels in Individuals Without Diabetes and With and Without Periodontitis Before and After Non‐Surgical Periodontal Therapy

Abstract: The HbA1c levels of individuals without diabetes and with periodontitis (group B) were significantly reduced 3 months after non-surgical periodontal therapy, although they never reached the same levels as those of the individuals without diabetes or periodontitis (group A).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 35 publications
2
22
1
1
Order By: Relevance
“…In accordance with our result, Perayil et al[26] in 2014, have reported that there was significant reduction in the HbA1c levels after NSPT in non diabetic individuals with periodontitis. The mean reduction in HbA1c levels obtained in the current study is comparable to the reduction reported by them.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with our result, Perayil et al[26] in 2014, have reported that there was significant reduction in the HbA1c levels after NSPT in non diabetic individuals with periodontitis. The mean reduction in HbA1c levels obtained in the current study is comparable to the reduction reported by them.…”
Section: Discussionsupporting
confidence: 93%
“…This observation connotes to the fact that, the average pocket depth had reduced to < 3 mm after NSPT and there by the overall surface area of the pocket lining which acts as a reservoir for periodontal pathogen and inflammatory markers had also reduced. This finding was in accordance with previous studies where significant pocket depth reduction had been observed after NSPT in non diabetic and diabetic patients[25,26]. In control group there was an increase in probing pocket depth and clinical attachment level.…”
Section: Discussionsupporting
confidence: 93%
“…This favors the explanation of the link between these two chronic diseases. Recently, studies have reported that nonsurgical periodontal treatment was sufficient to reverse even a prediabetes condition to a healthy state in a large proportion of the participants 34,35…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, individuals in our study had BMI values slightly less than overweight. It has been shown that nonobese individuals tend to show more decrease in HbA1c levels than obese individuals, as pronounced obesity masks the decrease in inflammatory response by periodontal therapy 34,44. The differences in study design may explain the variations in results in moderately controlled diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in 35 to 65 years old individuals with prediabetes, the HbA 1c level decreased significantly 3 months after nonsurgical periodontal treatment, namely from 6.08(AE0.23)% to 5.67(AE0.33)%. 70 Another small study of persons between 35 and 75 years old with prediabetes reported a clinically and statistically significant decrease in HbA 1c level 3 months after nonsurgical periodontal treatment, namely, from 6.08(AE0.51)% to 5.89(AE0.45)%. 71 Finally, among 66 persons with prediabetes, the HbA 1c level improved from an average of 6.0% (5.7%-6.3%) to 5.1% (4.9%-5.3%) in the 33 who received nonsurgical periodontal therapy only and from 6.2% (5.7%-6.4%) to 5% (4.8%-5.3%) in participants who additionally received oral doxycycline.…”
Section: Periodontal Treatment In Prediabetes: Effects On Blood Glucomentioning
confidence: 98%